Pengembangan Penelitian Pendidikan Agama Islam Bagi Pengawas: Model Penelitian Tindakan di Sekolah dan Kelas (Studi Kasus di Kabupaten Trenggalek) - Suyoto, Suyoto (Taallum: Jurnal Pendidikan Islam, 2016)
A supervisor must be competent research and development to improve the quality of education in schools or madrassa. Supervisors should also be able to assist teachers in preparing classroom action research, in addition he himself should also do research oversight. Supervisors are conducting research and development in order to fulfill their duties is a professional watchdog. The role of supervisors in implementing research and development in addition to conducting research for itself seeks a teacher in conducting action research.